Validation of evaluation items of physical activity knowledge for Physical Education in Primary Education (Research, Society and Development, 2019)
The purpose of this study was to elaborate and validate items for the evaluation of the knowledge of elementary school students about the effects of physical activity on the body, based on the Reference Matrix for Large Scale Cognitive Evaluation of the Contents of Physical Education in Primary Education (9th year) - ACEF9. The final version of the instrument was composed of 24 items, since only those that obtained a level of agreement among the judges of IVC> 0,80 were considered valid. The items are of multiple choice with four alternatives contemplating the following general contents: i) Physiology of the Exercise, ii) Introduction to Nutrition, iii) Physical Evaluation, iv) Anatomy and v) Biochemistry. Such contents on the effects of physical activity on the body are directly or indirectly based on the National Curricular Common Base and the National Curricular Guidelines of the undergraduate course in Physical Education. The instrument resulting from this research can be used by physical education teachers in elementary school to analyze and / or check students' knowledge about the effects of physical activity on the body. Finally, we suggest that the instrument for this validated study be applied to a group of students for construct analysis, as well as other validation studies of instruments similar to this one, with reference to the ACEF9 Matrix.